2017
DOI: 10.5606/tgkdc.dergisi.2017.14654
|View full text |Cite
|
Sign up to set email alerts
|

Aortic regurgitation and aortic valve operation in Takayasu arteritis: A meta-analysis

Abstract: ÖZAmaç: Bu çalışmada Takayasu arteriti olan hastaların majör bir komplikasyonu olabilen aort regürjitasyonunun klinik özellikleri ile beraber bu hastalarda gereken aort kapak ameliyatları tanımlandı.Ça lış ma pla nı: Bu meta-analiz; literatürden erişilen, Ocak 2001 ve Aralık 2016 tarihleri arasında yayınlanan ve 159 Takayasu arteriti hastasını içeren 41 ilgili yazıya dayandırıldı. On iki erkek ve 55 kadın hasta varken 92 hastanın cinsiyet bilgisi yoktu. Bul gu lar:Takayasu arteriti popülasyonunun aort regürjit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 46 publications
(236 reference statements)
0
1
0
Order By: Relevance
“…A recent meta-analysis also revealed that concurrent cardiac operation is a predictive factor of postoperative complications. [18] Moreover, aneurysmal change in the surgical site frequently occurs in patients with TAK and has been described as a cause of reoperation. [2,9] Eight of 24 patients (33.3%) who did not receive concomitant aortic root/arch replacement underwent reoperation and 5 of those 8 patients (62.5%) underwent Bentall's operation in their second operation.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis also revealed that concurrent cardiac operation is a predictive factor of postoperative complications. [18] Moreover, aneurysmal change in the surgical site frequently occurs in patients with TAK and has been described as a cause of reoperation. [2,9] Eight of 24 patients (33.3%) who did not receive concomitant aortic root/arch replacement underwent reoperation and 5 of those 8 patients (62.5%) underwent Bentall's operation in their second operation.…”
Section: Discussionmentioning
confidence: 99%